1964
DOI: 10.1139/o64-114
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Mustard Oil Glucosides: Iv. The Administration of Methionine-C14 and Related Compounds to Horseradish

Abstract: The administration of C14-labelled compounds to horseradish (Armoracia lapathifolia Gilib.) demonstrated that both methionine and acetate were efficiently incorporated into the aglycone (allyl isothiocyanate) of sinigrin. Chemical degradation of the aglycone showed that the methyl group of acetate appeared in the "isothiocyanate carbon" and that carbons 2, 3, and 4 of methionine were incorporated into carbons 2, 3, and 4 respectively of the aglycone with very little randomization. Homocysteine was the only oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…1). Early feeding experiments with radiolabeled amino acids and acetate (Chisholm and Wetter 1964;Serif 1968, 1970) suggested an outline for the pathway. This was confirmed by more detailed in vivo studies with stableisotope-labeled tracers (Graser et al 2000) and by isolation of a key intermediate (Chapple et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…1). Early feeding experiments with radiolabeled amino acids and acetate (Chisholm and Wetter 1964;Serif 1968, 1970) suggested an outline for the pathway. This was confirmed by more detailed in vivo studies with stableisotope-labeled tracers (Graser et al 2000) and by isolation of a key intermediate (Chapple et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Glucosinolates of six different chain lengths are produced in Arabidopsis. Studies with labeled Met and acetate have shown that elongation of the Met side chain involves a repetitive cycle of three reaction steps that result in the net addition of one methylene carbon for each turn of the cycle (Chisholm and Wetter, 1964;Serif, 1968, 1970;Graser et al, 2000). To enter the cycle, Met is first deaminated to the corresponding 2-oxo-acid, 4-methylthio-2-oxobutanoic acid.…”
mentioning
confidence: 99%
“…2) that convert 2-oxoisovalerate into Leu ( Fig. 1; Chisholm and Wetter, 1964;Matsuo and Yamazaki, 1968;Serif and Schmotzer, 1968;Graser et al, 2000). Each cycle of elongation is initiated by an aldol-type condensation between acetyl-CoA and a v-methylthio-2-oxo acid leading to the formation of a v-methylthioalkylmalate.…”
mentioning
confidence: 99%